PENGARUH TERPAAN IKLAN BAREKSA DI INSTAGRAM DAN KREDIBILITAS BRAND AMBASSADOR BOY WILLIAM TERHADAP MINAT GENERASI Z DALAM MENGGUNAKAN BAREKSA SEBAGAI PLATFORM INVESTASI ONLINE - Farhan Haritz, Abdullah; Setyabudi, Djoko; Ratri Rahmiaji, Lintang (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Investors in the capital market have experienced significant growth and are projected to continue increasing, with Generation Z dominating this growth. Bareksa, as a pioneering mutual fund investment application, has the potential to become the number one investment platform, especially for Generation Z. Bareksa has engaged in various marketing activities, such as advertising on Instagram and appointing Boy William as a brand ambassador. However, in reality, the majority of Generation Z is more interested in using Bibit rather than Bareksa. This study aims to determine the influence of advertisement exposure and brand ambassador credibility on the interest in using Bareksa. This research utilizes the strong advertisement theory and source credibility theory. The study uses non-probability and purposive sampling techniques with a total of 104 respondents, and data was collected using questionnaires. The data obtained were then tested using simple linear regression analysis. The hypothesis testing results indicate that Bareksa's advertisement exposure accounts for 15.5% with an influence magnitude of 0.063, and brand ambassador credibility accounts for 12.5% with an influence magnitude of 0.090 on the interest in using Bareksa. From the resul of the study, it can be concluded that the higher the advertisement exposure, the higher the interest in using Bareksa. Similarly, the higher the credibility of brand ambassador Boy William, the higher the interest in using Bareksa